2001
DOI: 10.1037/0022-006x.69.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance as a predictor of outcome and retention in the National Institute on Drug Abuse Collaborative Cocaine Treatment Study.

Abstract: The authors examined the relation between therapeutic alliance, retention, and outcome for 308 cocaine-dependent outpatients participating in the National Institute on Drug Abuse Collaborative Cocaine Treatment Study. High levels of alliance were observed in supportive-expressive therapy (SE), cognitive therapy (CT), and individual drug counseling (IDC), and alliance levels increased slightly but significantly from Session 2 to Session 5 in all groups. In contrast to other studies, alliance was not a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
98
3
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 16 publications
10
98
3
4
Order By: Relevance
“…It would appear plausible that if clients rate their relationship as less successful, this would be more likely to predict dropout than therapist ratings because the clients are the ones making the decision to leave treatment. What is more, a number of studies in the drugs field have reported such positive associations between the client rated alliance and retention or completion (Barber et al, 1999;Barber et al, 2001;De Weert-Van Oene et al, 1999;De Weert-Van Oene et al, 2001;Petry and Bickel, 1999). As the alliance was assessed at a similar time as in these studies, it is not clear why the results differ and why in this study it is the counsellor rated alliance that shows the greater predictive capability.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It would appear plausible that if clients rate their relationship as less successful, this would be more likely to predict dropout than therapist ratings because the clients are the ones making the decision to leave treatment. What is more, a number of studies in the drugs field have reported such positive associations between the client rated alliance and retention or completion (Barber et al, 1999;Barber et al, 2001;De Weert-Van Oene et al, 1999;De Weert-Van Oene et al, 2001;Petry and Bickel, 1999). As the alliance was assessed at a similar time as in these studies, it is not clear why the results differ and why in this study it is the counsellor rated alliance that shows the greater predictive capability.…”
Section: Discussionmentioning
confidence: 69%
“…client, counsellor or observer ratings of the alliance) should be used. For example, whilst observer, but not client and therapist, alliance ratings predicted retention in one study (Fenton et al, 2001), both client and therapist ratings predicted retention in other studies (Barber et al, 1999;Barber et al, 2001;De Weert-Van Oene et al, 1999;De Weert-Van Oene et al, 2001). In Petry & Bickel (1999)'s study, only therapist ratings, but not client ratings predicted the alliance.…”
Section: Introductionmentioning
confidence: 86%
“…10.111/j.1360-0443.2004.00935.x). Studies consistently found that better therapeutic alliance early in treatment predicts longer treatment retention or completion (Barber, Luborsky, Crits-Christoph, Thase, Weiss, Frank, Onken and Gallop 1999;Barber, Luborsky, Gallop, Crits-Christoph, Frank, Weiss, Thase, Connolly, Gladis, Foltz and Siqueland 2001;De Weert-Van Oene, De Jong, Jorg and Schrijvers 1999;De Weert-Van Oene, Schippers, De Jong and Schrijvers 2001;Fenton, Cecero, Nich, Frankforter and Carroll 2001;Luborsky, Barber, Siqueland, McLellan and Woody 1995;Petry & Bickel 1999;Simpson et al 1997). Positive relationships have also been reported between a good therapeutic relationship and client engagement Fiorentine, Nakashima and Anglin 1999;Simpson et al 1997) and reduced in-treatment drug use (Gerstley 1988;Simpson et al 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Counselors are key players in both the delivery of treatment, especially in regard to their ability to affect client engagement (e.g., Barber et al, 2001;Joe, Simpson, Dansereau, & Rowan-Szal, 2001;Martin, Garske, & Davis, 2000;Simpson & Joe, 2004), and the transfer process of evidence-based interventions into clinical practice (e.g., Knudsen & Roman, 2004;Knudsen, Ducharme, Roman, & Link, 2005). Indeed, their views of the treatment program as a workplace and its social norms also are associated with the treatment experiences and progress of their clients (e.g., Broome et al, this issue;Moos & Moos, 1998), as well as their own job engagement and satisfaction (e.g., Maslach, Shaufeli, & Leiter, 2001).…”
mentioning
confidence: 99%